A Discussion on the Ecological Position of Sal (Shorea robltsta) in Central India - Hewetson, C. E. (Indian Forester, 1953)
The article discusses the ecological problems of the distribution of Sal in Central India. The main distribution of the sal is probably controlled by climate but within its range the distribution depends mostly on edaphic factors. It is pointed out that no simple explanation in terms of physical or chemical factors is adequate and directs attention to lines of research which might lead to progress.